Balung Kulon Community Economic Empowerment Strategy Through Waste Management of Units of Enterprises Owned by Balung Kulon Village - Syaifuddin Yahya; Abdul Wadud Nafis; Abdul Rokhim (Department of Islamic Economics, Postgraduate Program, UIN Kiai Haji Achmad Siddiq, Indonesia, 2024)
BUMDes Karya Mandiri in Balung Kulon Village, Jember Regency, has developed a waste management unit as a strategy for community economic empowerment. This initiative aims to transform previously valueless waste into a source of income and a means to enhance community self-reliance. The study aims to describe the implementation of waste management by BUMDes Karya Mandiri and the strategies applied to empower the community through this unit. The research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Research subjects were selected purposively, and data analysis was conducted descriptively using source triangulation as a validity technique. The results show that waste management is carried out through the segregation of organic and inorganic waste by households, schools, offices, and the general public. The management process follows the 3R principles (reduce, reuse, recycle), although the effort to apply the